Health Campaign to Prevent High Sugar Intake Among West Java Teenagers - Michelle Gracia Nathanael; Elizabeth Wianto; Riki Himawan Mulyadi (IMAGIONARY, 2026)
sweet foods and beverages among teenagers in West Java. It addresses a common issue among adolescents the tendency to consume sugary intake excessively, despite being aware of its negative effects. The purpose of this study is to encourage a healthier and more balanced lifestyle among teenagers who habitually consume excessive amounts of sweet foods and drinks. The data collection methods used include interviews, structured analysis, questionnaire distribution to teenagers in the West Java region, and literature review. This study applies theories related to campaigns, healthy lifestyles, communication, and media, structured through the AISAS approach (Attention, Interest, Search, Action, Share). The campaign visuals are designed in the form of photography and cartoon illustrations, incorporating metaphorical elements to strengthen the message being delivered. Through this final project, it is hoped that the health campaign can positively influence the lifestyle of teenagers in West Java, making it healthier and of higher quality